Pengaruh Spiritualitas Tempat Kerja terhadap Kesejahteraan Karyawan dengan Identifikasi Organisasi dan Kelincahan Tenaga Kerja sebagai Faktor Intervensi - Sumampouw, Ruland Willy Jack; Wibisana, Satria Arif; Primadini, Adinda (Lembaga Penelitian Universitas YARSI, 2025)
The purpose of this study is to analyze the influence of workplace spirituality on employee wellbeing with organizational identification and workforce agility as mediating variables, respondents in this study were workers who worked as salesmen in the automotive industry The method used in this study is a quantitative method. The results of this study state that: workplace spirituality has a negative and insignificant effect on employee wellbeing. Workplace spirituality has a positive and significant effect on organizational identification. There is a positive and significant influence between workplace spirituality and workforce agility. Organizational identification has a positive and significant effect on employee wellbeing. Workforce agility has a positive and significant effect on employee wellbeing. Organizational identification mediates the relationship between workplace spirituality and employee wellbeing. Workforce agility mediates the relationship between workplace spirituality and employee wellbeing. Managerial implications need to improve the practice of spirituality in the workplace by strengthening employee identification with the organization and developing work agility (workforce agility), because both have been proven to significantly improve employee wellbeing even though spirituality itself does not have a direct impact.